Osteoporosis, Fractures, and Bone Mineral Density Screening in Veterans With Kidney Stone Disease. (3rd March 2021) - Ganesan, Calyani; Thomas, I‐Chun; Romero, Ruth; Song, Shen; Conti, Simon; Elliott, Chris; Chertow, Glenn M; Tamura, Manjula Kurella; Leppert, John T; Pao, Alan C
ABSTRACT: Whether a link exists between kidney stone disease and osteoporosis or fractures remains an open question. In this retrospective cohort study, we sought to determine the prevalence of osteoporosis and fractures and rate of bone mineral density screening by dual‐energy X‐ray absorptiometry (DXA) in patients with kidney stone disease. We examined nationwide data from the Veterans Health Administration and identified 531, 431 patients with kidney stone disease between 2007 and 2015. Nearly 1 in 4 patients (23.6%, 95% confidence interval [CI] 23.5–23.7) with kidney stone disease had a prevalent diagnosis of osteoporosis or fracture. In patients with no prior history of osteoporosis or bone mineral density assessment before a kidney stone diagnosis, 9.1% were screened with DXA after their kidney stone diagnosis, of whom 20% were subsequently diagnosed with osteoporosis. Our findings provide support for wider use of bone mineral density screening in patients with kidney stone disease, including middle‐aged and older men, a group less well recognized as at risk for osteoporosis or fractures. © 2021 American Society for Bone and Mineral Research (ASBMR).